Noise indicators for corona acoustic signal from power lines - estimation in intensified interference conditions - WSZOŁEK, Tadeusz (Archives of Acoustics, 2009)
In the spectrum of corona acoustic signal two characteristic components can be distinguished: (1) tonal components - higher harmonics of the network frequency and (2) noise component, observed in the frequency band extending above 1 kHz. On the other hand the total intensity of that signal is relatively low - up to 50dB at 15m distance from the outmost conductor - and it is strongly dependent on the environmental conditions. Thus the nature of that signal is essentially random. Because of the above-mentioned features, in practice the best evaluation method of the negative environmental impact is a continuous signal monitoring. Unfortunately for such a procedure some problems are encountered with automated extraction of the parameters (indicators) normally used for evaluation of the signal's acoustic annoyance, especially in intensified interference conditions. One of the more efficient methods of filtering out the random interference signals is the statistic spectrum measurement method. In this work a practical realization is described for estimation of corona noise indicators, making use of the statistic spectrum measurement. High efficiency of such an approach has been shown, especially in favorable weather conditions, when the acoustic signal of corona process is relatively low, while the random interference level may be intensified.